RETROSPECTIVE STUDY: INITIAL PHARMACOTHERAPY PROFILE OF NEW ACNE VULGARIS PATIENTS - Esravila Ariya Wibisono; Diah Mira Indramaya; Maftuchah Rochmanti (Jurnal Berkala Epidemiologi, 2020)
Background: Acne Vulgaris (AV) is one of the most common diseases in the field of dermatology and ranks as the eighth most prevalent disease worldwide. Early management of this potentially deforming skin disease may reduce the pathophysiological burden and improve the quality of life of patients. Purpose: This study aimed to determine the pharmacotherapy for new patients with AV. Methods: This cross-sectional study used new patients with AV of the Cosmetic Division of the Outpatient Skin and Venereal Health Unit, Regional Public Hospital (RSUD) Dr. Soetomo, from January to December 2013 that were descriptively presented. The variable was the pharmacotherapy given. This study used secondary data collection by looking at the patients’ medical records. The variables studied were acne lesions and pharmacotherapy regimens, including the administration route and the medicine used. Results: The number of samples that met the inclusion criteria was 951 patients. Comedonal acne was most commonly given topical tretinoin. Papulopustular acne was most commonly given a topical combination of clindamycin and tretinoin, while acne conglobata was most commonly given a combination of topical clindamycin and tretinoin with oral doxycycline. Conclusion: The new patients with comedonal acne were mostly prescribed topical tretinoin pharmacotherapy. A pharmacotherapy combination of topical clindamycin and tretinoin was given to most new patients with papulopustular acne, whereas new patients with conglobata acne were given a pharmacotherapy combination of topical tretinoin and clindamycin with oral doxycycline.